Constitutive Reprogramming of Fibroblast Mitochondrial Metabolism in Pulmonary Hypertension - Plecitá-Hlavatá, Lydie; Tauber, Jan; Li, Min; Zhang, Hui; Flockton, Amanda R; Pullamsetti, Soni Savai; Chelladurai, Prakash; D'Alessandro, Angelo; El Kasmi, Karim C; Ježek, Petr; Stenmark, Kurt R (American journal of respiratory cell and molecular biology, 2016)
Remodeling of the distal pulmonary artery wall is a characteristic feature of pulmonary hypertension (PH). In hypoxic PH, the most substantial pathologic changes occur in the adventitia. Here, there is marked fibroblast proliferation and profound macrophage accumulation. These PH fibroblasts (PH-Fibs) maintain a hyperproliferative, apoptotic-resistant, and proinflammatory phenotype in ex vivo culture. Considering that a similar phenotype is observed in cancer cells, where it has been associated, at least in part, with specific alterations in mitochondrial metabolism, we sought to define the state of mitochondrial metabolism in PH-Fibs. In PH-Fibs, pyruvate dehydrogenase was markedly inhibited, resulting in metabolism of pyruvate to lactate, thus consistent with a Warburg-like phenotype. In addition, mitochondrial bioenergetics were suppressed and mitochondrial fragmentation was increased in PH-Fibs. Most importantly, complex I activity was substantially decreased, which was associated with down-regulation of the accessory subunit nicotinamide adenine dinucleotide reduced dehydrogenase (ubiquinone) Fe-S protein 4 (NDUFS4). Owing to less-efficient ATP synthesis, mitochondria were hyperpolarized and mitochondrial superoxide production was increased. This pro-oxidative status was further augmented by simultaneous induction of cytosolic nicotinamide adenine dinucleotide phosphate reduced oxidase 4. Although acute and chronic exposure to hypoxia of adventitial fibroblasts from healthy control vessels induced increased glycolysis, it did not induce complex I deficiency as observed in PH-Fibs. This suggests that hypoxia alone is insufficient to induce NDUFS4 down-regulation and constitutive abnormalities in complex I. In conclusion, our study provides evidence that, in the pathogenesis of vascular remodeling in PH, alterations in fibroblast mitochondrial metabolism drive distinct changes in cellular behavior, which potentially occur independently of hypoxia.
Keywords: Mitochondria; kyselina pyrohroznová; Oxidative Phosphorylation; Glycolysis; Humans; Paracrine Communication; oxidativní fosforylace; buněčné dýchání; superoxidy; Down-Regulation; parakrinní signalizace; Chronic Disease; oxidace-redukce; Superoxides; makrofágy; Citric Acid Cycle; glykolýza; Lung; Phenotype; Hypoxia; lidé; mitochondrie; zvířata; Hypertension, Pulmonary; plíce; down regulace; hypoxie; Energy Metabolism; Pyruvic Acid; plicní hypertenze; Cattle; energetický metabolismus; Pyruvate Dehydrogenase Complex; chronická nemoc; fenotyp; Electron Transport Complex I; skot; citrátový cyklus; pyruvátdehydrogenasový komplex; Oxidation-Reduction; respirační komplex I; fibroblasty; Animals; Cellular Reprogramming; Macrophages; Fibroblasts; přeprogramování buněk; Cell Respiration